Steatocystoma multiplex: A case report of a rare entity - Shin, Nan-Young; Kang, Ju Hee; Kim, Jo-Eun; Symkhampa, Khantaly; Huh, Kyung-Hoe; Yi, Won-Jin; Heo, Min-Suk; Lee, Sam-Sun; Choi, Soon-Chul (Imaging science in dentistry, 2019)
Steatocystoma multiplex is an uncommon benign skin disease, which typically manifests as numerous intradermal cysts that can be scattered anywhere on the body. Although usually asymptomatic, it can be significantly disfiguring. One type of steatocystoma multiplex is known to be associated with the autosomal dominant inheritance of a mutation in the gene coding for keratin 17 ( ). In such cases, it is often concurrent with other developmental abnormalities of the ectoderm-derived tissues, such as the nails, hair, and teeth. To the best of our knowledge, few cases have been reported of steatocystoma multiplex of the oral and maxillofacial region. This report describes a case of steatocystoma multiplex of both sides of the neck and multiple dental anomalies, with a focus on its clinical, radiological, and histopathological characteristics, as well as the possibility that the patient exhibited the familial type of this condition.